Cognitive evoked potentials in the diagnosis of post-concussion syndrome due to blast mild traumatic brain injury - Zavaliy, Yurii V.; Solonovych, Oleksandr S.; Biloshitsky, Vadym V.; Trеtiakova, Albina I.; Chebotariova, Lidia L.; Suliy, Liudmyla M. (Ukrainian Neurosurgical Journal, 2021)
Hostilities in the East of Ukraine are characterized by the use of new weapons, including rocket artillery, rocket-propelled grenades and landmines. This has led to an increase in the number of victims with blast mild traumatic brain injury (BMTBI) and the need to provide them with effective assistance and rehabilitation. An important task is to improve the BMTBI diagnosis by specifying the objective criteria for structural and functional disorders of the central nervous system. This will improve the prognosis of the course of BMTBI in the injured and the treatment program, including personalized, to prevent the development of persistent neurological deficit. Objective: to investigate the possibilities of the cognitive evoked potentials (CEP) method for the objective diagnosis of cognitive disorders in post-concussion syndrome (PCS) BMTBI. Materials and methods. The study involved 115 men with PCS (main group) and 30 healthy individuals (control group). The cognitive functions of the study participants were studied using the questionnaire "Cicerone". The neurophysiological method for assessing the functional state of the brain involved the registration of CEP, event-related (P300 CEP). Results. The selection of a subgroup of patients with PCS, characterized by a predominance of cognitive impairments, allowed us to trace the relationship between the results of neurophysiological studies with the cognitive indicators of patients with BMTBI. P300 latency indices are inversely proportional to cognitive assessment the questionnaire "Cicerone" and statistically significantly depend on the severity of cognitive impairment. Conclusions. The CEP P300 method can be an effective means of objectifying the degree of cognitive impairment in patients with PCS due to BMTBI.